Ratna Sagar Private Limited - Dixit, Mukund R., (SAGE knowledge. Cases., 2016)
The case presents the efforts of Dr Dhanesh Jain, founder of Ratna Sagar Publications, to innovate in children's publishing space. His innovations received mixed response. Commercial success was delayed. Adoption of innovations by the educational institutions did not happen as expected but the innovations, however, created opportunities for other business ventures. Dr Jain is wondering whether the innovation efforts were worth their while.